Awareness and Involvement of the Arts, Commerce and Science College Teachers in Students’ Mental Health and Behavioural Problems: A Cross-sectional Study from Sangli District (MH), India - Waghachavare, Vivek Baliram; Chavan, Manohar Shankarrao; Gore, Alka Dilip; Dhumale, Girish Bhimrao (IIUM Medical Journal Malaysia, 2017)
Background: Teachers play an important role in reducing adolescent health problems. However, the involvement of teachers in adolescent health is not well understood. This current study was conducted to address this. Methods: A cross-sectional study was conducted among teachers of randomly selected arts, commerce and science colleges in Sangli, (Maharashtra) India. The data was collected by cluster random sampling. The study period was from November 2014 to April 2015. The study tool was self-administered questionnaire. Due ethical considerations, consents were taken. Analysis was done using Microsoft Excel 2003 and IBM SPSS version 22. Results: Out of 319 study participants; 246 (77.1%) participants had good awareness regarding adolescent health problems, 254 (79.6%) participants had good attitude towards reproductive health. Forty-three (13.5%), 22 (6.9%) and 15 (4.7%) participants had good practices regarding behavioural problems, psychological problems and substance abuse respectively. Practices about behavioural problems and substance abuse were associated with adolescent health training. In bi-variate analysis, age was a significant predictor for all the three practices. Conclusion: Most teachers had good attitude and awareness; but poor knowledge and practices regarding adolescent issues. All teachers should undergo training regarding adolescent health; with periodic refresher courses or lectures. Anonymous feedback from students should be sought to keep vigilance over efforts of the teachers.